Electrical Conduction Mechanism in Ferrocene - Shahi, Kalpana; Srinivasan, K.V.; Sharan, Abha; Srinivasan, Padmavathy (Asian Journal of Chemistry, 2016)
Electrical conduction in ferrocene has been studied using a ‘sandwich’ type of cell in DC and AC fields. Space charge limited conduction in DC and orientation polarization in AC have been observed.